Distribution of cervical abnormalities detected by visual inspection with acetic acid in Swaziland, 2011-2014: a retrospective study - Ginindza, TG; Almonte, M; Dlamini, X; Sartorius, B (AOSIS, 2018)
Background: Cervical cancer is the fourth most common cancer worldwide among women, with the number of new cases increasing from 493 243 in 2002 to 527 000 in 2012. These numbers are likely to be underestimated because given the lack of registration resources, cervical cancer deaths are usually under-reported in low-income countries.